PENGARUH GAYA BELAJAR DAVID KOLB (DIVERGER, ASSIMILATOR, CONVERGER, ACCOMMODATOR) TERHADAP HASIL BELAJAR SISWA PADA MATERI PENCEMARAN LINGKUNGAN - Azrai, Eka Putri; Ernawati, E; Sulistianingrum, Gita (Universitas Negeri Jakarta, 2017)
Learning style is a complex way that someone feels most effective and efficient in learning. David Kolb divides learning style into four groups, there are diverger, assimilator, converger, and accommodator. The research aimed to know the influence of David Kolb’s learning style (diverger, assimilator, converger, accommodator) to students learning outcomes in Environmental Pollution. This research was conducted at 105 Senior High School of Jakarta on April - May 2016. The method that used in this research was Ex Post Facto with survey technique. The sample determination for each learning styles based on learning style groups that have less number of students. The sample that used for each learning styles was 11 students. Based on this research, these four learning styles have different average learning outcome. Prerequisite test showed that data normally distributed and homogenously. Based on the hypothesis test used one-way ANOVA, known that cognitive, affective, and psychomotor learning outcomes have Fcount > Ftable, so that H0 was rejected on 0,05 significant level. It means there is influence of David Kolb’s learning style (diverger, assimilator, converger, accommodator) to students learning outcomes in Environment Pollution.